2020
DOI: 10.1021/acsami.0c06674
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Responsive Lanthanide-Based Hydrogel with Encryption, Naked Eye Sensing, Shape Memory, Self-Healing, and Antibacterial Activity

Abstract: In this work, we reported a multi-responsive luminescent hydrogel with properties of encryption, naked eye sensing of glucose, shape memory, self-healing, and antibacterial activity. The hydrogel (GA/CCS/DNSA/Eu3+) was obtained by mixing phenylboronic acid-modified gelatin (GA-DBA), catechol-modified carboxymethyl chitosan (CCS-PCA), 3,5-dinitrosalicylic acid (DNSA), and Eu3+ ions through a facile heating–cooling process. The resultant hydrogel exhibits reversible luminescence and color and phase changes in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 82 publications
1
50
0
Order By: Relevance
“…To this end, recently, stimuli-responsive materials have received tremendous attention and have been considered as promising mediums for data security applications [12][13][14][15][16][17][18][19] . Exploiting the unique reactive properties of these smart materials, various data encryption platforms have been designed employing carbon dots composite 20 , mechanochromic hydrogel 21 and luminescent hydrogel 22 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, recently, stimuli-responsive materials have received tremendous attention and have been considered as promising mediums for data security applications [12][13][14][15][16][17][18][19] . Exploiting the unique reactive properties of these smart materials, various data encryption platforms have been designed employing carbon dots composite 20 , mechanochromic hydrogel 21 and luminescent hydrogel 22 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…They can be extensively used in various applications, such as optoelectronics devices, eld-effect transistors, detectors, medical diagnosis, bio-imaging, etc. [112][113][114]. Hence, luminescent gels have been paid much attention due to their outstanding biocompatibility and viscoelastic properties [115].…”
Section: Anti-counterfeiting Applicationsmentioning
confidence: 99%
“…124 For instance, a hydrogel with triple shape memory properties was obtained by combining the formation of reversible Schiff base bonds between the amino groups of CS and aldehyde groups of oxidized dextran, which was applied to memorize temporary shapes, with the chelation effect of various metal cations which fixed other temporary shapes. 125 A great example of the immense possibilities that combining natural polymers with dynamic covalent chemistry offer is found in the work recently published by Zhou et al 126 They reported a multi-responsive luminescent hydrogel prepared by mixing phenylboronic acidmodified gelatin, catechol-modified carboxymethyl chitosan, 3,5-dinitrosalicylic acid, and Eu 3+…”
Section: Technological Applicationsmentioning
confidence: 99%